Cross-cultural differences in IQ test performance: extension of an existing normative database on WAIS-III test performance - Gaylard, Emma K (Rhodes University, Faculty of Humanities, Department of Psychology, 2006)
Prior research (Shuttleworth-Edwards et al., 2004) presented preliminary normative data for the Wechsler Adult Intelligence Scale "“ III (WAIS-III) for Southern Africa, stratified according to gender (female vs. male), language (black African vs. white English), level of education (matric/12+ years of education vs. Graduate/15+ years of education) and quality of education (disadvantaged "“ Department of Education and Training vs. advantaged - Private/Model C). IQ scores for black African language and white English Southern Africans were comparable with the United States of America (USA) standardization when level and quality of education were equitable. ('White English' is the term used to denote those of European descent whose first language is English). A limitation of the research was the lack of control for language for most of the black groups and particularly in the Private/Model C Graduate group, where sixty percent of the participants originated from Zimbabwe. These represented a particularly elite group whose education was equitable to that of the white participants throughout their education (i.e. at primary, secondary and tertiary level). In order to rectify the lack of homogeneity of language, all non- Xhosa first language participants were excluded from the black sample and sixteen additional Xhosa first language participants were tested on the WAIS-III. Data analyses found no significant differences between the original and new groups, except in the comparison between Mixed African language Private/Model C Graduates and the Xhosa first language Private/Model C Graduate/15+ years of education, where there was a lowering of WAIS-III subtest, index and IQ scores in the newly constituted group. This lowering in test performance is explained in that the new Xhosa first language 15+ years of education group was a less advantaged group than the original Mixed African Language Private/Model C Graduate group, as the new group generally had less advantaged primary school education and had generally studied less at a tertiary level. Overall, these results demonstrate an incremental increase in WAIS-III test performance for sample groups on a continuum of quality of education from least to most advantaged education. This was true for both verbal and non-verbal subtests.
Keywords: Wechsler Adult Intelligence Scale; Wechsler Adult Intelligence Scale -- South Africa; Black people -- Education; Black people -- Social conditions; Intelligence tests -- South Africa